Analisis Model Pembelajaran Menulis Kreatif Dalam Menulis Puisi Pada Siswa SMP Negeri 2 Meranti Kabupaten Asahan - Tetty Romauli Panjaitan; Panigoran Siburian; Wahyu Ningsih; Hijrah Purnama Sari Ariga (Educatio, 2026)
Indonesian language learning in schools has an important role in developing students' language skills, both orally and in writing. The purpose of this study is to find out the application of creative writing learning and students' ability to write poetry through the creative writing learning model applied by teachers. The type of research used in this study is qualitative research. This research was carried out at SMP Negeri 2 Meranti, Asahan Regency in the seventh grade of the 2025–2026 school year. The research sample was 29 students. Primary and secondary data sources. Data collection techniques through observation, documentation and interviews. The results of the research on the use of creative learning both from the teacher aspect and from the student aspect are that both achieve success. From the teacher's aspect, in the learning process using creative learning, the Indonesian language teacher in grade VII of SMP Negeri 2 Meranti Asahan Regency who is involved in learning to write poetry has done it with a good predicate qualification. The results of grade VII students of SMP Negeri 2 Meranti, Asahan Regency in writing poetry using creative learning, it can be seen that the average overall score of students with good predicates means that students have been able to master the learning. Student grades vary greatly, ranging from less-very good. The ability of students with a very good predicate is that there are 12 students with a good predicate, namely there are 0 students, students with a fairly good predicate, namely 5 students and the ability of students with a low predicate, namely there are 2 students